Dipteran diversity and succession pattern on carcass of rabbits treated with opium dross: Implication in forensic medicine - davood keshavarz; Yavar Rassi; Mohamadali Oshaghi; KOUROSH AZIZI; SAYENA RAFIZADEH; MARZIEA SHAHRIARINAMADI (Society for Indonesian Biodiversity, 2020)
Abstract. Keshavarz D, Rassi Y, Oshaghi MA, Azizi K, Rafizadeh S, Shahriarinamadi M. 2020. Dipteran diversity and succession pattern on carcass of rabbits treated with opium: Implication in forensic medicine. Biodiversitas 21: 3135-3141. The present study aimed to investigate the effect of opium on the succession pattern and diversity of Diptera on rabbit carcasses. In the present experimental study, dipteran species were collected from rabbit carcasses during the decay process. During this study, two replicates were performed, and four rabbits were used in each. Rabbits divided equally into two groups. In the first group, animals were received 25 mg opium dross orally via a gastric tube and then gradually increased the dose to 100 mg/case/day, while the second group were used as controls and received distilled water. The most frequent species on both carcass types were Chrysomya albiceps (26.2%), Lucilia sericata (15.9%), and Musca domestica (13.9%). Diversity analysis indicates high species richness on untreated carcasses (Shannon: 2.1; Margalef: 1.7). However, a significant difference was not detected for the Shannon index between the treated and untreated carcasses (P: 0.56). The taxa similarity values for sampling intervals ranged from 0.20-0.46 for both untreated and treated carcasses. Permutation analysis showed that successional patterns of dipteran species were similar between opium dross-treated and untreated carcasses. Therefore, in the case of opioid (opium) abused cadaver, this substance could not have an effect on the PMI estimation based on the pattern of succession. But it seems that the PMI should be corrected when the estimate is based on larval growth rate.